How Much Do Schools and Districts Matter? A Production Function Approach to School Accountability - James L. Phelps; Michael F. Addonizio (Educational Considerations, 2006)
In 1989, President George H.W. Bush convened a first-ever education summit in Charlottesville, Virginia, with the governors of the states and territories.